The Floating Production, Storage and Offloading Vessel Design for Oil Field Development in Harsh Marine Environment - Akandu, Ezebuchi; Incecik, Atilla; Barltrop, Nigel (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2015)
The oil and gas exploration and production activities in deep sea are now on a steady increase globally. Therefore, it is necessary to design a cost effective and safe system for these operations. The main objective of this research is to design a Floating Production, Storage and Offloading (FPSO) vessel suitable for operation even in extreme meteorological and oceanographic conditions. In order to achieve this, the effects of extreme environmental loads on the vessel have been evaluated in terms of the maximum responses in surge, heave and pitch modes of motion. Furthermore, an interactive programme, the Principal Dimensions Programme (PD Prog) has been designed to accurately evaluate and optimise the principal particulars based on the required storage capacity and response analyses. Results show that the vessel length, which is directly proportional to the cube root of the cubic number (the overall volume), is a measure of the critical wavelength. Close to the critical wavelength in extreme metocean condition, the vessel could be subjected to several billions Newton meter of Wave Bending Moment. This design technique, in addition to the numerous useful data obtained, helps to ensure good performance during operation and so reduces downtime, and increases uptime, safety and operability of the vessel even under extreme metocean conditions.